Balloon Cinch Deformity during Angioplasty Procedures: An Indication for Impending Rupture1. Issue 2 (1st October 2013) - Salman, Loay; Castro, Hector; Vazquez‐Padron, Roberto I.; Monrroy, Mauricio; Abdelwahed, Yehia; Rizvi, Abid; Duque, Juan; Akmal, Muhammad Usman Talha; Merrill, Donna; Nayer, Ali; Asif, Arif
Abstract Percutaneous transluminal balloon angioplasty (PTA) is a commonly performed procedure for hemodialysis vascular access dysfunction including thrombosis. While PTA is generally safe, balloon rupture during the procedure is a potential complication. Because such a rupture can cause damage to the blood vessel, indication of an imminent balloon rupture might help avoid such a complication. This analysis reports on six PTA procedures that were complicated by balloon rupture. All cases demonstrated terminal (caudal/cranial) cinch deformation. There was a loss of sharp terminal tapering and its replacement with banana silhouette before the balloon rupture. Importantly, the contour deformation and balloon rupture occurred at a pressure that was lower than the rated burst pressure. The cinch deformity can be used as an indication for impending balloon rupture. We suggest deflation of balloons that demonstrate shape deformations to avoid vascular injury.